Lektura anagramatyczna a przekład (zmagania translatorskie z wierszem Krešimira Bagicia la folie de saussure) - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2015)
The anagram reading and the problem of translation (struggles with a translation of the poem la folie de saussure by Krešimir Bagić) The starting point for the presented elaboration on translation is the concept of Ferdinand de Saussure’s anagrams. Anagrams consist of certain phoneme or group of phonemes repeated in the literary work. They form a certain word or words (idea, theme) which are scattered (disseminated) in the text. By reconstructing these words we are able to discover or (re)construct the implicit, hidden sense of the text. Reading and interpreting anagrams from the perspective of psychoanalysis enables one to consider them as an expression of the author’s unconsciousness (Julia Kristeva). In this paper the translation of the poems (la folie de saussure by K. Bagić) is analyzed taking into consideration the possibilities and limitations of the transfer of hidden and added senses that appears as a result of the anagram’s presence or the tonal organization of the literary text (e.g. in the case of the poetry of the Russian Futurists and the idea of zaum). Key words: anagram, Ferdinand de Saussure, Julia Kristeva, Krešimir Bagić, unconsciousness